Eurasian Cooling Linked to the Vertical Distribution of Arctic Warming - He, Shengping; Xu, Xinping; Furevik, Tore; Gao, Yongqi (Geophysical Research Letters, 2020)
Observations show that deep Arctic winter warming, extending from surface to mid‐troposphere, has concurred with below‐average temperature over central Eurasia. Modeling studies focusing on the response to Arctic sea ice loss have shown Arctic surface warming but no consistent atmospheric changes at midlatitude. Using a large number of simulations from coupled and uncoupled climate models, we show that Eurasian below‐average temperatures are more frequent in winters with deep warming compared to shallow, near‐surface warming over the Barents‐Kara Seas. Dramatic weakening of the midlatitude jet stream and increase in Ural blocking frequency are more likely to occur in winters with deep Arctic warming. Deep warming is independent of sea ice forcing but follows increased poleward atmospheric energy and moisture advection from the North Atlantic to the Arctic, indicating that internal natural variability and not sea ice is the main driving forcing for deep Arctic warming‐cold Eurasia pattern in historical simulations. publishedVersion